Information Security Awareness in Sub-Saharan African Schools: The Role of Educational Leadership in Turbulent Times - (:unkn) unknown (My University, 2025)
The COVID-19 pandemic has influenced the increased adoption of digital tools in educational institutions across sub-Saharan Africa. The efficient flow of information within modern organizations heavily depends on using Information and Communication Technology (ICT). Like other organizations, the education sector has experienced a growth in the use of ICT, which has brought about potential threats to information security and users’ safety. In this regard, school leadership can play a pivotal role in ensuring information security by raising users’ awareness. Consequently, protecting school information systems and their users’ safety should be a top priority for school heads and other stakeholders. This paper aims to analyze different strategies school leadership can implement to raise information security awareness (ISA) among staff, teachers, and students and to develop a framework for sub-Saharan African schools considered newcomers in using information and communication technologies. This chapter focuses on the transformational leadership theory, the technology acceptance model (TAM), and the knowledge, attitude, behavior (KAB) model.
Keywords: African Research